Revisiting the "starved gut" hypothesis in inflammatory bowel disease. Issue 1 (10th January 2023) - Colgan, Sean P.; Wang, Ruth X.; Hall, Caroline H.T.; Bhagavatula, Geetha; Lee, J. Scott
Abstract : Active episodes of inflammatory bowel disease (IBD), which include ulcerative colitis and Crohn's disease, coincide with profound shifts in the composition of the microbiota and host metabolic energy demand. Intestinal epithelial cells (IEC) that line the small intestine and colon serve as an initial point for contact for the microbiota and play a central role in innate immunity. In the 1980s, Roediger et al proposed the hypothesis that IBD represented a disease of diminished mucosal nutrition and energy deficiency ("starved gut") that strongly coincided with the degree of inflammation. These studies informed the scientific community about the important contribution of microbial-derived metabolites, particularly short-chain fatty acids (SCFA) such as butyrate, to overall energy homeostasis. Decades later, it is appreciated that disease-associated shifts in the microbiota, termed dysbiosis, places inordinate demands on energy acquisition within the mucosa, particularly during active inflammation. Here, we review the topic of tissue energetics in mucosal health and disease from the original perspective of that proposed by the starved gut hypothesis.